The brain as a structure: A model of how fluid–structure interactions stiffen brain tissue after injury. (1st April 2022) - Feng, Yuan; Chen, Yu; Yao, Yifei; Li, Xiaowei; Zhang, Aili; Genin, Guy M.
Highlights: A fluid–structure interaction model was constructed to explain the tissue stiffening effect of brain tissue after injury. Radius, flow speed, and connectivity of cerebral vessels affect tissue stiffness in a way that produces spatial heterogeneity in tissue properties, and can thus lead to local stress amplification. Abstract: The brain contains a tree of vasculature that contributes not only oxygen and nutrients but also structural integrity to the brain parenchyma. The structure formed by this vasculature affects the mechanical response of brain tissue both before and after injury, and maybe a determinant of an individual's injury susceptibility. To investigate structural changes of brain tissue after injury, we constructed an idealized representative volume element model of fluid–structure interactions within brain parenchyma and applied it to study how vessel size, cerebral spinal fluid (CSF) flow velocity, and CSF flow networks relate to previous experimental observations of healthy and injured brain tissue. We hypothesized that injury-associated structural changes to the neurovasculature may alter the mechanical responses of brain tissue and predispose an individual to subsequent injury. Parameters representing the mechanics of uninjured and injured brain tissue were verified against experimental characterizations of these tissue in uniaxial compression and shear. Results supported our hypothesis, and highlight the importance of considering cerebral vasculature as a structure in predicting and analyzing the brain's response to mechanical loading.